INFLUENCE OF POLICY IMPLEMENTATION, LEADERSHIP AND PROFESSIONALISM TOWARD THE PERFORMANCE OF MANPOWER DINES OF BEKASI CITY WEST JAVA PROVINCE - Wahyu Tri Putranto; Wirman Syafri; Prio Teguh; Irwan Tahir (Dinasti Publisher, 2022)
The phenomenon that is used as the object of research is the performance of the Bekasi City Manpower Office. The purpose of the study was to discuss the effect of Policy Implementation, Leadership and Professionalism on the Performance of the Bekasi City Manpower Office. The research uses quantitative research. The research sample was 242 respondents taken from a population of 667 people using the Krejcie Table. Data collection techniques using literature study, questionnaire and observation techniques. Data analysis using SEM analysis. The results of the study are as follows: The magnitude of the influence of Policy Implementation on the Performance of the Bekasi City Manpower Office reached 0.30, which was weak but significant. The magnitude of the influence of leadership on the performance of the Bekasi City Manpower Office reached 0.52, which is quite strong and significant. The magnitude of the influence of professionalism on the performance of the Bekasi City Manpower Office reached 0.33, which was weak but significant. The new concept that can be compiled from the discussion of the results of research on the effect of Policy Implementation on the Performance of the Bekasi City Manpower Office is a new concept on Financial Governance of Regional Work Units; regarding the Leader of Organizational Behavior Steering; and about Professional Appearance.